2023
DOI: 10.3390/biomedicines11102791
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Anti-Inflammatory Parameters in PCOS Patients Depending on Body Mass Index: A Case-Control Study

Elena Vasyukova,
Ekaterina Zaikova,
Olga Kalinina
et al.

Abstract: Background: it has been suggested that chronic low-grade inflammation plays an important role in the pathogenesis of polycystic ovary syndrome (PCOS). According to previous studies, it remains unclear which cytokines influence the development of this syndrome and whether their increase is associated with the presence of excess weight/obesity or is an independent factor. The aim of our research was to determine the parameters of chronic inflammation in women with PCOS in comparison with healthy women in the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Elevation in macrophage inflammatory protein (MIP-1α) was also seen in PCOS, which accords with the increased levels of MIP-1α reported previously in women with PCOS [ 38 ]. MIP-1α/CCL3 is an inflammatory chemokine produced by cells during infection or inflammation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Elevation in macrophage inflammatory protein (MIP-1α) was also seen in PCOS, which accords with the increased levels of MIP-1α reported previously in women with PCOS [ 38 ]. MIP-1α/CCL3 is an inflammatory chemokine produced by cells during infection or inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…Two CVRPs correlated with 1,25(OH) 2 D 3 in the control cohort. The CVRPs that were elevated and those that were correlated to vitamin D in PCOS were associated with inflammation and the immune response, as evidenced by STRING protein–protein interactions; this would accord with the chronic low-level inflammation that may be involved in the pathogenesis of PCOS [ 37 ], and that is not influenced by the presence of excessive weight or obesity [ 38 ]. These results would suggest that the alterations in CVRPs are both an inherent feature of PCOS that are likely indicative of early inflammation as well as due to changes in vitamin D metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Elena Vasyukova et al examined the serum levels of cytokines in PCOS patients and age-matched females without PCOS. As a result, the serum concentration of CD40 in PCOS patients was significantly higher than that in controls (27). Multiple studies have shown that CD40 was significantly highly expressed in patients with hyperthyroidism and contributed to GD pathogenesis in several pathways (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…These results were consistent with previous studies that obesity could induce chronic low-grade inflammation in PCOS patients ( 36 ). One previous study showed that IL-12 and TNFα levels in the plasma were increased in PCOS patients compared to controls ( 37 ), and another study revealed the correlation between follicular fluid IL-12 levels and increased T-lymphocyte numbers in the PCOS patients ( 38 ). TNF signaling is known to have an essential role in the pathogenesis of PCOS.…”
Section: Discussionmentioning
confidence: 99%